Morphological Characteristics of Dicrocoelium dendriticum (Digenea, Dicrocoeliidae), Parasitizing Three Host Species in the Central Regions of Ukraine - O. V. Kruchynenko; S. M. Mykhailiutenko; O. S. Klymenko; N. S. Kanivets; L. M. Korchan (Zoodiversity, 2020)
Distribution of trematodes of the species Dicrocoelium dendriticum (Rudolphi, 1819) Looss, 1899 (Digenea: Dicrocoeliidae) parasitizing cattle (Bos taurus Linnaeus, 1758), sheep (Ovis aries Linnaeus, 1758) and goat (Capra aegagrus hircus Linnaeus, 1758) was studied in the Poltava and Kirovohrad regions of Ukraine. The recorded prevalence of infection is 26.9 % in cattle, 28.42 % in sheep and 24.5 % in goat. D. dendriticum is the only species of the genus Dicrocoelium which infects domestic animals in the central regions of Ukraine. The trematodes obtained from cattle are significantly different from those isolated from sheep and goat by length, width and area of body, and length of vitelline ducts.